Histopathology of Rhipicephalus sanguineus (Acari: Ixodidae) ticks fed on resistant hosts - Veronez, Viviane Aparecida [UNESP]; de Castro, Marcio Botelho; Bechara, Gervasio Henrique [UNESP]; Szabo, Matias P. J. [UNESP] (Springer, 2010)
Histological features of Rhipicephalus sanguineus ticks fed on dog, a non resistant host, and on guinea pig, a resistant host, were compared. Unfed ticks and ticks from each host species were collected during first and third infestation and processed for histology. Many ticks from guinea pigs, especially during third infestation, were unattached, dehydrated and small. Only the midgut of ticks fed on guinea pigs had host leukocytes. Vacuolization of midgut cells was observed in all ticks, with exception of those fed on dogs for more than 96 h. Ticks of guinea pigs, particularly from third infestation, had vacuolated tracheae and swelling of malpighian tubules. Solely ticks from third infestation of guinea pigs displayed vacuolization of oocytes. Ticks fed on guinea pigs also had an increased number of guanine spherules. Observed alterations in ticks from guinea pigs are discussed.
Keywords: Rhipicephalus sanguineus; Histopathology; Resistance; guinea pig; Dog